2010
DOI: 10.1128/jcm.01463-09
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Mycobacterium tuberculosis and Rifampin Resistance by Use of On-Demand, Near-Patient Technology

Abstract: Current nucleic acid amplification methods to detect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
797
4
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 837 publications
(874 citation statements)
references
References 49 publications
30
797
4
21
Order By: Relevance
“…The rapid inactivation is in line with findings from Daum et al (2014), which showed that PS-MTM is an effective medium to inactivate a pure culture of M. tuberculosis at ~10 6 CFU/ml at an exposure time of 30 minutes. This is a similar effect as achieved by the Xpert SR buffer where an 8 and 9 log reduction was demonstrated at 15 minutes and 2 hours respectively (Helb, et al, 2010). A minimum time of 60 minutes from collection to specimen processing is likely to be routine and will provide a safe specimen for downstream testing, particularly in resource-constrained settings.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The rapid inactivation is in line with findings from Daum et al (2014), which showed that PS-MTM is an effective medium to inactivate a pure culture of M. tuberculosis at ~10 6 CFU/ml at an exposure time of 30 minutes. This is a similar effect as achieved by the Xpert SR buffer where an 8 and 9 log reduction was demonstrated at 15 minutes and 2 hours respectively (Helb, et al, 2010). A minimum time of 60 minutes from collection to specimen processing is likely to be routine and will provide a safe specimen for downstream testing, particularly in resource-constrained settings.…”
Section: Discussionsupporting
confidence: 59%
“…However, the only relevant published data on the effect of reagents added directly to sputum on the viability of TB bacilli is the sample reagent buffer (SR) of the Xpert assay. The SR has demonstrated capability of producing an 8 log reduction, within 15 minutes, in M. tuberculosis viability in sputum spiked with this organism (Helb et al, 2010). In M. tuberculosis-positive sputum specimens, with bacillary loads of less than 10 7 colony forming units/milliliter (CFU/ml), total inactivation was achieved within 15 minutes (Banada et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although sputum smear test is quicker and produces results in about 30 min, it can only detect 10% to 75% of TB cases and requires trained microscopists. In developing countries, the technical expertise and tools needed to perform these tests are limited, and TB is often not diagnosed or treated early, which allows the disease to spread quickly in crowded living quarters and to build resistance to the drugs used in the treatment of the infection [17,18] .…”
Section: Discussionmentioning
confidence: 99%